Attitudes of students with learning disability towards the use of distance learning in the presence of the Coronavirus pandemic in Kuwait - Al-Saeedi, Ahmad Mohsen (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the level of attitudes of secondary students with learning disability towards the use of the distance learning system in light of the spread of coronavirus (COVID-19) in Kuwait, the sample of the study consisted of (32) male and female students with learning disabilities at the secondary level. A questionnaire consisting of(23) paragraph and distributed on(3) axes, the results found that the attitudes of students with learning disabilities at the secondary level towards the use of distance learning were positive, with a moderate degree, where the general average was (2.32), with a percentage of (77%). The axis (feelings towards distance learning) ranked first, with an average of (2.37) and a percentage of (79%), followed by the axis (advantages towards distance learning), with an arithmetic average of (2.31), percentage of(77%) while the axis(turnout towards the distance learning) last rank in average (2.29) with a percentage of (76%). The results did not reveal any statistical differences in the level of students' attitudes of learning disability towards distance learning by holding courses, improving the learning environment and distributing brochures that show the importance of using distance learning in teaching.
Keywords: Attitudes; Learning disability; distance learning